2009
DOI: 10.1007/s00128-009-9903-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Kinetics of β-Cyfluthrin and Imidacloprid in Brinjal and Soil Under Subtropical Conditions of Punjab, India

Abstract: Dissipation of beta-cyfluthrin and imidacloprid was studied following three applications of a combination formulation of Solomon 300 OD (beta-cyfluthrin 9% + imidacloprid 21%) @ 60 and 120 g a.i. ha(-1) at 7 days interval. Samples of brinjal were collected at 0, 1, 3, 5, 7, 10 and 15 days after the last application and residues of beta-cyfluthrin and imidacloprid were estimated on gas liquid chromatography (GLC) and high performance liquid chromatography (HPLC), respectively. Half-life periods for beta-cyfluth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…Accordingly, the half live of beta-cyfluthrin, varying between 1.07 and 2.41 days irrespective of fruits, is lower as compared to imidacloprid (1.98-3.30 days), which seem to be related to greater photolability of the former (Spurlock and Lee 2008). The half live of imidacloprid in brinjal recorded as 3.30 and 2.64 days at lower and higher doses, agrees well with the report of Mandal et al (2010). The dissipation pattern of imidacloprid and beta-cyfluthrin when compared to different fruits under study produced a similar rank order with greater persistence in brinjal followed by tomato and okra.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Accordingly, the half live of beta-cyfluthrin, varying between 1.07 and 2.41 days irrespective of fruits, is lower as compared to imidacloprid (1.98-3.30 days), which seem to be related to greater photolability of the former (Spurlock and Lee 2008). The half live of imidacloprid in brinjal recorded as 3.30 and 2.64 days at lower and higher doses, agrees well with the report of Mandal et al (2010). The dissipation pattern of imidacloprid and beta-cyfluthrin when compared to different fruits under study produced a similar rank order with greater persistence in brinjal followed by tomato and okra.…”
Section: Resultssupporting
confidence: 81%
“…The initial deposit of imidacloprid and beta-cyfluthrin, dependent on dosage applied, varies between 0.27 and 1.20 mg kg -1 with the increasing order in okra [ brinjal [ tomato and 0.04 and 0.28 mg kg -1 with the highest amount in tomato followed by okra and brinjal respectively. The comparison of initial deposits obtained in the present study with earlier reports (Mohapatra et al 2011;Mandal et al 2010;Mukherjee et al 2007;Gupta et al 2008) is made difficult by the differences in rates of application as well as vegetables concerned. The difference in rank order of initial deposit with respect to fruits and insecticides is probably related to differences in interaction between insecticide and fruits as determined by nature of the chemical and surface properties of fruit cuticle (Bates 1990).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The results also showed that the maximum pest suppression was brought out by the first 25 days after the treatment thereafter the efficacy of the solomon treatment was decline. This phenomenon was expected because Mandal et al, 2010 [7] had reported that imidacloprid and beta-cyfluthrin have a very short half life with the half value of 1.39 and 1.74 days respectively. This effect might be attributing to the fact that pepper is a crop of hot humid tropics and its characteristic climatic requirements are high rainfall and temperature and high relative humidity.…”
Section: Efficacy Of Solomom Against Pepper Pest Infestationmentioning
confidence: 84%
“…In order to control the residue of imidacloprid in chrysanthemum buds and flowers, it is necessary to realize the behavior of imidacloprid in chrysanthemum buds, flowers and cultivated soil. By now, there are some reports on degradation of imidacloprid in soil, fruits, vegetable and other crops (Ju et al 2006;Lou et al 2004;Guan et al 2010;Rouchaud et al 1994;Miles Inc 1993;Scholz and Spiteller 1992;Baskaran et al 1999;Kousik Mandal et al 2010;Thai et al 2009;Sherif et al 2008;Ayman et al 2007;Parshotam et al 2009;Sanyal et al 2006). However, no any report about residue and degradation of imidacloprid in chrysanthemum buds, flowers and their cultivated soil were found.…”
mentioning
confidence: 99%